Pengaruh Pemberian Berbagai Macam Pupuk terhadap Pertumbuhan dan Hasil Tanaman Gumitir (Tagetes erecta L.) - I NYOMAN INDRA BAYU NATA; I PUTU DHARMA; I KETUT ARSA WIJAYA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
The Effect of Giving Various Kinds of Fertilizer on Growth and Yield of Gumitir Plants (Tagetes Erecta L.) Gumitir flower is one of the flowers used for ritual facilities by Balinese Hindus, besides it is used for tourism purposes. One of the efforts to increase growth and development as well as the quality of gumitir products is to provide adequate and balanced nutrient supply through fertilization. The purpose of this study was to analyze the effect of giving various kinds of fertilizer on growth and yield of gumitir plants (Tagetes erecta L.). This study used a Randomized Block Design with four replications and six treatments namely TP (without fertilizer), PG (Gandasil B fertilizer), PN (NPK Mutiara fertilizer), PU (Urea fertilizer), PB (Bio Urine fertilizer), and PS (fertilizer SP-36). The parameters observed were plant height (cm), number of branches per plant (fruit), time of flower buds appearing (days), fresh flower weight (g), diameter per flower (cm), number of fresh flowers per plant (grains), total weight of fresh flowers per plant (kg), fresh crop weight per plant (g), and oven dry perchart weight per plant (g). The results showed the type of fertilizer treatment gave a real effect on all observed variables. The NPK pearl fertilizer treatment yielded the highest total fresh flower weight per plant which was 2.15 kg, a markedly higher increase of 65.11% compared to the treatment without fertilizer and 53.48% compared with Bio Urine but not significantly different from the treatment of SP-36 fertilizer, Gandasil B fertilizer and Urea fertilizer.